Impact of Image Filters and Observations Parameters in CBCT for Identification of Mandibular Osteolytic Lesions. (22nd August 2012) - Monteiro, Bruna Moraes; Nobrega Filho, Denys Silveira; Lopes, Patrícia de Medeiros Loureiro; de Sales, Marcelo Augusto Oliveira
Abstract : The aim of this study was to analyze the influence of filters (algorithms) to improve the image of Cone Beam Computed Tomography (CBCT) in diagnosis of osteolytic lesions of the mandible, in order to establish the protocols for viewing images more suitable for CBCT diagnostics. 15 dry mandibles in which perforations were performed, simulating lesions, were submitted to CBCT examination. Two examiners analyzed the images, using filters to improve image Hard, Normal, and Very Sharp, contained in the iCAT Vision software, and protocols for assessment: axial; sagittal and coronal; and axial, sagittal and coronal planes simultaneously (MPR), on two occasions. The sensitivity and specificity (validity) of the cone beam computed tomography (CBCT) have been demonstrated as the values achieved were above 75% for sensitivity and above 85% for specificity, reaching around 95.5% of sensitivity and 99% of specificity when we used the appropriate observation protocol. It was concluded that the use of filters (algorithms) to improve the CBCT image influences the diagnosis, due to the fact that all measured values were correspondingly higher when it was used the filter Very Sharp, which justifies its use for clinical activities, followed by Hard and Normal filters, in order of decreasing values.